The effectiveness of logistics management in providing an efficient lead-time management for export distribution / Siti Hawa Talib - Talib, Siti Hawa (Faculty of Business and Management, 1999)
The functions of Logistics Management is very important whether we realise it existence or not. We cannot deny its importance in our life by making necessity goods and wants reliable when demanded. The Effectiveness of Logistics Management in Providing An Efficient Lead-time Management For Export Distribution brings to the 'scenario of the functions and importance of logistics management for export distribution. This study is related to the effectively managing the logistics elements in order to achieve shorter lead-time management for customer order delivery. The flow of information related to the customer order is required to be managed effectively in order to achieve an efficient logistics management. Besides managing the flow of information, the physical movement also required to be managed properly. When discussing the physical movement of goods, warehousing is the other elements which are related directly. Managing warehouses are important especially if we know the highly risk works of loading goods for export. The final stage or process is occur at the warehouse. Therefore proper checking activities should be planned and handled by the persons responsible in warehouse activities. Finally, besides managing warehouse, other departments which concerned with the export distribution should be integrated, Success cannot be achieved without the integration of all departments.